Мультифрактальный анализ биоразнообразия и ценотической структуры сообщества растений по данным дистанционного зондирования - Артюшенко, М.В.; Зуб, Л.Н.; Подгородецкая, Л.В.; Федоровский, А.Д. (Доповіді НАН України, 2011)
Обгрунтовано використання мультифрактальної моделі опису різноманіття вищої водної рослинності водойм. На прикладі оз. Світязь розглянуто застосування методів дистанційного зондування як ефективного засобу збирання просторово-розподілених даних для аналізу структури угруповання асоціацій і верифікації моделі. Наведено опис різноманіття фітоценозів макрофітів озера, визначено мультифрактальні властивості структури угруповань. The proof of the multifractal model application for describing the diversity of communities of higher aquatic plants in reservoirs is given. On the example of Lake Svityaz, the application of remote sensing techniques is considered as an effective means to collect spatially distributed data to analyze the structure of plant community associations and to perform the model verification. The description of the diversity of the phytocenoses of macrophytes of Lake Svityaz is given, and the multifractal properties of a plant community structure are demonstrated.